การปรับปรุงการยึดติดของฟิล์มแคลเซียมฟอสเฟตบนไทเทเนียมซับสเตรตที่ถูกดัดแปรผิวด้วยวิธีเคมีไฟฟ้า - สิริธิดา ชูเกษร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Improving the adhesion of calcium phosphate film on titanium substrate was performed in three different kind of modified surface solutions: H[subscript 2]O[subscript 2], HCl, NaOH. The pure titanium metal (99.99%) with 0.8x2 cm was used as a substrate for electrochemical deposition. The substrate was etched in 2 M-HF for 1 minute before electrochemical deposition process. The calcium phosphates film could be formed in a negative regions of current density at -10 mA/cm[superscript 2] for 5 minute. The electrolyte used in this experiment was MCPM based 20% V/V ethanol. The major phase appeared in the titanium substrate with H[subscript 2]O[subscript 2] modified surface was monetite co-existed with brushite. The best adhesion of calcium phosphate film to substrate formed on 4 M H[subscript 2]O[subscript 2] treated titanium substrates was 7.06 MPa. After soaking in C-SBF, R-SBF and n-SBF for 1-7 days, only monetite phase still appeared.